Superflous Symbols

Algebra Level 3

x ( x + y + z ) = 26 y ( x + y + z ) = 27 z ( x + y + z ) = 28 \begin{array}{c} x(x+y+z)=26 \\ y(x+y+z)=27 \\z(x+y+z)=28 \end{array}

How many triplets of real numbers ( x , y , z ) (x,y,z) satisfy the system of equations above?


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Otto Bretscher
May 29, 2016

Relevant wiki: System of Equations - Substitution

Adding up gives ( x + y + z ) 2 = 26 + 27 + 28 = 81 (x+y+z)^2=26+27+28=81 , so x + y + z = ± 9 x+y+z=\pm 9 and ( x , y , z ) = ± ( 26 9 , 27 9 , 28 9 ) (x,y,z)=\pm\left(\frac{26}{9},\frac{27}{9},\frac{28}{9}\right) . There are 2 \boxed{2} solutions.

Hung Woei Neoh
May 29, 2016

x ( x + y + z ) = 26 x(x+y+z)=26\implies Eq.(1)

y ( x + y + z ) = 27 y(x+y+z)=27\implies Eq.(2)

z ( x + y + z ) = 28 z(x+y+z)=28\implies Eq.(3)

Notice that for these equations, x , y , z x,y,z and ( x + y + z ) (x+y+z) all cannot be 0 0 . Therefore, it is safe to divide these equations:

Eq.(2) ÷ \div Eq.(1):

y ( x + y + z ) x ( x + y + z ) = 27 26 y x = 27 26 \dfrac{y(x+y+z)}{x(x+y+z)} = \dfrac{27}{26}\\ \dfrac{y}{x} = \dfrac{27}{26}

y = 27 26 x y=\dfrac{27}{26}x\implies Eq.(4)

Eq.(3) ÷ \div Eq.(1):

z ( x + y + z ) x ( x + y + z ) = 28 26 z x = 28 26 \dfrac{z(x+y+z)}{x(x+y+z)} = \dfrac{28}{26}\\ \dfrac{z}{x} = \dfrac{28}{26}

z = 28 26 x z=\dfrac{28}{26}x\implies Eq.(5)

Substitute Eq.(4) and Eq.(5) into Eq.(1):

x ( x + 27 26 x + 28 26 x ) = 26 x ( 26 + 27 + 28 26 x ) = 26 81 26 x 2 = 26 x 2 = 2 6 2 81 x = ± 2 6 2 81 = ± 26 9 x\left(x+\dfrac{27}{26}x + \dfrac{28}{26}x \right)=26\\ x\left(\dfrac{26+27+28}{26}x\right) = 26\\ \dfrac{81}{26}x^2=26\\ x^2 = \dfrac{26^2}{81}\\ x=\pm \sqrt{\dfrac{26^2}{81}} = \pm \dfrac{26}{9}

When x = 26 9 x=\dfrac{26}{9}

y = 27 26 ( 26 9 ) = 27 9 = 3 z = 28 26 ( 26 9 ) = 28 9 y=\dfrac{27}{26} \left(\dfrac{26}{9}\right) = \dfrac{27}{9} = 3 \quad\quad\quad z=\dfrac{28}{26} \left(\dfrac{26}{9}\right) = \dfrac{28}{9}

When x = 26 9 x=-\dfrac{26}{9}

y = 27 26 ( 26 9 ) = 27 9 = 3 z = 28 26 ( 26 9 ) = 28 9 y=\dfrac{27}{26} \left(-\dfrac{26}{9}\right) = -\dfrac{27}{9} = -3 \quad\quad\quad z=\dfrac{28}{26} \left(-\dfrac{26}{9}\right) = -\dfrac{28}{9}

The solutions are: ( x , y , z ) = ( 26 9 , 3 , 28 9 ) , ( 26 9 , 3 , 28 9 ) (x,y,z)=\left(\dfrac{26}{9},3,\dfrac{28}{9}\right),\;\left(-\dfrac{26}{9},-3,-\dfrac{28}{9}\right)

Number of triples that satisfies the equations = 2 = \boxed{2}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...